Greenhouse Gas Emissions From Native and Non-native Oysters - McCarthy, Gretchen J.; Ray, Nicholas E.; Fulweiler, Robinson W. (Frontiers in Environmental Science, 2019)
Non-native species introductions are associated with a range of ecosystem changes such as habitat destruction, competition with native species, and biodiversity losses. Less well known is the role non-native species play in altering biogeochemical processes, such as the emission of greenhouse gases (GHGs). In this study we used laboratory incubations to compare seasonal (spring, summer, fall) emissions of the GHGs nitrous oxide (N2O), methane (CH4), and carbon dioxide (CO2) from native (Crassostrea virginica) and non-native (Ostrea edulis) oysters collected from a northern temperate estuary (Duxbury Bay, Massachusetts, USA). We observed strong seasonal signals in GHG fluxes, where C. virginica was the higher GHG emitter, and produced on average twice as much N2O (0.39 nmol g-1 dry tissue weight hr-1) and twenty times as much CH4 (1.31 nmol g DTW-1 hr-1) compared to O. edulis (0.16 nmol N2O g DTW-1 hr-1 and 0.07 nmol CH4 g DTW-1 hr-1). C. virginica also had significantly (p < 0.001) higher summer maximum production rates of CO2 compared to O. edulis (53.4 mol g DTW-1 hr-1 and 45.4 mol g DTW-1 hr-1, respectively). Despite these differences, chlorophyll-a consumption rates between the species were similar (p = 0.95). These results suggest that the non-native O. edulis is a lower GHG emitter than the native C. virginica and highlight that, at least in terms of GHG emissions, this non-native species introduction may not be detrimental to the environment.